Media reporting and business cycles: Empirical evidence based on news data - Michael Lamla; Sarah M. Lein-Rupprecht; Jan-Egbert Sturm (University of Basel, Center of Business and Economics (WWZ), 2019)
Recent literature suggests that news shocks could be an important driver of economic cycles. In this article, we use a direct measure of news sentiment derived from media reports. This allows us to examine whether innovations in the reporting tone correlate with changes in the assessment and expectations of the business situation as reported by firms in the German manufacturing sector. We find that innovations in news reporting affect business expectations, even when conditioning on the current business situation and industrial production. The dynamics of the empirical model confirm theoretical predictions that news innovations affect real variables such as production via changes in expectations. Looking at individual sectors within manufacturing, we find that macroeconomic news is at least as important for business expectations as sector-specific news. This is consistent with the existence of information complementarities across sectors.
Keywords: E32; D82; 330; media reporting; news-driven business cycles; sectoral information complementarities